Peningkatan Kualitas Bacaan Al-Qur’an melalui Metode Talaqqi di TBM Hajah Ambo: Improving the Quality of Qur'anic Reading Through the Talaqqi Method at TBM Hajah Ambo - Khoirun Nidhom; Mila Kamila; Ida Kurnia Shofa; M Fahrel Hidayat (Khadimul Mujtama’: Journal of Community Service, 2026)
This community service was motivated by the partner’s problem at TBM (Reading Park) Hajah Ambo in Patramanggala Village, Kemiri District, Tangerang Regency, namely the low quality of students’ Qur’anic reading, especially in letter pronunciation (makharij), mad, and ghunnah, as well as the unstructured memorization system. The objective was to improve the quality of reading and the quantity of Qur’anic memorization of 23 children aged 7-12 years through the application of the talaqqi method. The implementation methods included initial observation, intensive mentoring for 8 weeks (June–July 2025) in three stages (reading improvement, memorization quality improvement, memorization quantity addition), and evaluation using pretest, posttest, and summative exams. Success indicators: a minimum 30% increase in reading quality score and a target of 5 children memorizing Surah An-Naba’ (40 verses). Results showed that the average reading quality score increased from 54.2 to 81.6 (50.6% increase). A total of 5 children (21.7%) succeeded in memorizing 40 verses, 3 children (13.0%) memorized 25 verses, and 15 children (65.2%) memorized 20 verses. The talaqqi method effectively improved the pronunciation of letters such as dzal and jim and increased learning motivation. Real impacts: students became more disciplined in memorization deposits and teachers began applying this method independently. Recommendations for follow-up: advanced training for teachers and addition of assistant staff.